KUALITAS PELAYANAN PADA BISNIS RUMAH SAKIT - JENITA JENITA (Maqdis: Jurnal Kajian Ekonomi Islam, 2016)
The research theme is the concept of business according to Islamic economics. This study aimed to determine the conformity level between the quality of services provided by the Pekanbaru Bhayangkara Hospital and inpatients’ expectation. The studying method used was descriptive and explanatory survey method. Descriptive survey of the study was a method to obtain a description of the services’ quality of the Pekanbaru Bhayangkara hospital and Explanatory survey is a method was implemented through distributing questionnaires to inpatients in the Pekanbaru Bhayangkara Hospital. This study was included in the crosssectional category, the entire inpatient population amounted to 1729 people with 95 people as a sample, and the sampling technique was purposive random sampling. The data analysis was Importance Performance Analysis, if there any gaps between the quality of services provided by the Pekanbaru Bhayangkara Hospital and inpatients’ expectation. The results showed that the quality of services is the organization's performance and obtained an average of respondents’ expectations for service in the Pekanbaru Bhayangkara Hospital was 3.97 which indicates the service is important, while the average of servicesin reality in Pekanbaru Bhayangkara Hospital was 3.09 which indicates patients was quite satisfied, and the level of conformity of the most respondents’ expectations was77.96% for the services in Pekanbaru Bhayangkara Hospital. It means that the quality of servicesis very important and be a main priority for Pekanbaru Bhayangkara Hospital, despite the fact that patients are not satisfied or quite satisfied with the services provided by the hospital.